2020
DOI: 10.1101/2020.10.14.337642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Boolean Model of the Formation of Tumour Associated Macrophages in anin-vitroModel of Chronic Lymphocytic Leukaemia

Abstract: The tumour microenvironment is the collection of cells in and surrounding cancer cells in a tumour including a variety of immune cells, especially neutrophils and monocyte-derived macrophages. In a tumour setting, macrophages encompass a spectrum between a tumour-suppressive (M1) or tumour-promoting (M2) state. The biology of macrophages found in tumours (Tumour Associated Macrophages) remains unclear, but understanding their impact on tumour progression is highly important. In this paper, we perform a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…One of the limitations in the study of TAMs is the difficulty in identifying them in bulk tumour samples, due to their close similarity with other macrophages that are also present in the TME. However, we showed that although NLCs and M2-type macrophages display a similar profile in the CLL microenvironment (6), some distinctions can be highlighted, such as high expression of the RAGE membrane receptor, the HIF1𝞪 and VEGF/EGF transcription factors in NLCs (7). Given the nurturing properties of NLCs in the CLL microenvironment, a high number of NLCs has been reported to lead to disease progression and shorter overall survival (8), (9).…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations in the study of TAMs is the difficulty in identifying them in bulk tumour samples, due to their close similarity with other macrophages that are also present in the TME. However, we showed that although NLCs and M2-type macrophages display a similar profile in the CLL microenvironment (6), some distinctions can be highlighted, such as high expression of the RAGE membrane receptor, the HIF1𝞪 and VEGF/EGF transcription factors in NLCs (7). Given the nurturing properties of NLCs in the CLL microenvironment, a high number of NLCs has been reported to lead to disease progression and shorter overall survival (8), (9).…”
Section: Introductionmentioning
confidence: 99%